Formation And Development Stages Of The Youth Union Of Uzbekistan As A Non-Governmental Organization (Zien Journal of Social Sciences and Humanities, 2025)
This article highlights the emergence of the Youth Union of Uzbekistan as a non-governmental organization, its historical roots, socio-political significance, and its role in shaping civic responsibility among young people. It also analyzes the organization’s transformations during the years of independence, its legal foundations, and its contribution to increasing social activity in society.